Attitudes of Teachers to Using Information and Communication Technology in Teaching – Advantages and Obstacles - Biljana Novković Cvetković; Zvezdan Arsić; Dragan Cenić (International Journal of Cognitive Research in Science, Engineering and Education, 2022)
This paper analyses the attitudes of teachers to using information and communication technology in teaching. The study was conducted on a sample of 269 teachers in the Republic of Serbia. The purpose of this research is to look at the intensity of ICT use in teaching, as well as to identify the benefits and obstacles that teachers face when using this technology. The study was based on a descriptive research methodology. Surveying and scaling techniques were used to measure the attitudes of teachers. It was concluded that teachers often use ICT in teaching. The greatest advantage of ICT use, as seen by teachers, is improved quality of teaching, a possibility to deliver interesting lessons and quick and easy access to information. The greatest obstacles emphasized by teachers were underdeveloped competencies of teachers, limited access to ICT in schools and insufficient trust in the use of new technologies.